Plasma Glucagon-Like Peptide-1 and Cholecystokinin Responses to Fast Food in Healthy-Weight and Obese Men - Handayani, Dian; Putri, Dianita Setya Pradita; Sujuti, Hidayat; Andarini, Sri; Rahmawati, Widya; Kusumastuty, Inggita; Harti, Leny Budhi; Sabrina, Nindy (Jurnal Kedokteran Brawijaya, 2020)
Satiety hormones play a role in obesity metabolism. The satiety response to similar nutrients in food in healthy and obese men remains undefined. The research was aimed to determine the satiety response differences by comparing the effect of isocaloric fast-food consumption on reducing appetite-related gut hormones, such as glucagon-like fullness ratings and both GLP-1 and CCK among healthy and obese men. Respondents were given an isocaloric fast food, then GLP-1 and CCK levels were measured using enzyme-linked immunosorbent assay (ELISA). Visual analogue scale (VAS) form was used for hunger and fullness ratings of the subjects. The difference level of GLP-1, CCK, and VAS between groups were measured by t-test. The correlation between VAS hunger and fullness rating was measured by Pearson. Plasma hormone levels in 16 obese and 16 healthy-weight respondents were assessed before eating and at 30, 60, and 120 minutes after consumption. In obese men, GLP-1 levels were significantly higher than those in healthy-weight men at 60 and 120 minutes, while healthy-weight men had significantly higher CCK levels than those of obese men over time (all p<0.05). The total area under the curve (AUC) for GLP-1 was significantly higher for obese men than for healthy-weight men, while the AUC for CCK was significantly higher for healthy-weight men than for obese men. Obese men have higher plasma GLP-1 levels and lower plasma CCK than healthy men indicates that those respondents were experiencing glucose intolerance and leptin alteration. The hormonal systems that may contribute to the development of obesity need further investigation.